Thioredoxin fusion construct enables high-yield production of soluble, active matrix metalloproteinase-8 (MMP-8) in Escherichia Coli - McNiff, M.L. (Protein Expr Purif, 2016)
Matrix metalloproteinases (MMPs) are crucial proteases in maintaining the health and integrity of many tissues, however their dysregulation often facilitates disease progression. In disease states these remodeling and repair functions support, for example, metastasis of cancer by both loosening the matrix around tumors to enable cellular invasion and by affecting proliferation and apoptosis, and they promote degradation of biological restorations by weakening the substrate to which the restoration is attached. As such, MMPs are important therapeutic targets. MMP-8 participates in cancer, arthritis, asthma and failure of dental fillings. MMP-8 differs from other MMPs in that it has an insertion that enlarges its active site. To elucidate the unique features of MMP-8 and develop selective inhibitors to this therapeutic target, a stable and active form of the enzyme is needed. MMP-8 has been difficult to express at high yield in a soluble, active form. Typically recombinant MMPs accumulate in inclusion bodies and complex methods are applied to refold and purify protein in acceptable yield. Presented here is a streamlined approach to produce in E. coli a soluble, active, stable MMP-8 fusion protein in high yield. This fusion shows much greater retention of activity when stored refrigerated without glycerol. A variant of this construct that contains the metal binding claMP Tag was also examined to demonstrate the ability to use this tag with a metalloprotein. SDS-PAGE, densitometry, mass spectrometry, circular dichroism spectroscopy and an activity assay were used to analyze the chemical integrity and function of the enzyme.